2015
DOI: 10.1111/1365-2656.12337
|View full text |Cite
|
Sign up to set email alerts
|

In hot and cold water: differential life‐history traits are key to success in contrasting thermal deep‐sea environments

Abstract: Summary Few species of reptant decapod crustaceans thrive in the cold‐stenothermal waters of the Southern Ocean. However, abundant populations of a new species of anomuran crab, Kiwa tyleri, occur at hydrothermal vent fields on the East Scotia Ridge.As a result of local thermal conditions at the vents, these crabs are not restricted by the physiological limits that otherwise exclude reptant decapods south of the polar front.We reveal the adult life history of this species by piecing together variation in micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 50 publications
5
58
0
1
Order By: Relevance
“…SMS deposits form through hydrothermal activity and exhibit a patchy distribution along seafloor tectonic margins, with deposits occurring on average every 100 km along the oceanic plate boundaries (Hannington et al, 2011). Active deposits support chemosynthetic communities restricted to hydrothermally active areas; many of these hydrothermal fauna have limited distributions and are endemic to one region, such as the crab Kiwa tyleri, endemic to the East Scotia Ridge in the Southern Ocean (Marsh et al, 2012(Marsh et al, , 2015 and the gastropod Ifremeria nautilei, restricted to three basins in the southwest Pacific (Bouchet and Warén, 1991;Thaler et al, 2011). Such limited distributions make these species particularly vulnerable to disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…SMS deposits form through hydrothermal activity and exhibit a patchy distribution along seafloor tectonic margins, with deposits occurring on average every 100 km along the oceanic plate boundaries (Hannington et al, 2011). Active deposits support chemosynthetic communities restricted to hydrothermally active areas; many of these hydrothermal fauna have limited distributions and are endemic to one region, such as the crab Kiwa tyleri, endemic to the East Scotia Ridge in the Southern Ocean (Marsh et al, 2012(Marsh et al, , 2015 and the gastropod Ifremeria nautilei, restricted to three basins in the southwest Pacific (Bouchet and Warén, 1991;Thaler et al, 2011). Such limited distributions make these species particularly vulnerable to disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for this remain unknown, but may relate to the highly un stable thermal and chemical conditions prevailing at vent chimneys, with regard to steep chemical and thermal gradients (Fisher et al 1988, Desbruyeres et al 2001, Luther et al 2001, which may negatively affect embryogenesis. Given low female fecundity (maximum N = 175 and N = 207 developing embryos, at E2 and E9, respectively; Marsh et al 2015) and the high maternal investment into offspring demonstra ted here, optimising reproductive success appears key to the species' ecology. Larval and early juvenile lecithotrophy, as discussed earlier, enables the species to employ a hypometabolic developmental mode of life whilst off the vent site.…”
Section: Physiological Constraints On Development and Dispersalmentioning
confidence: 88%
“…Ovigerous females retrieved were found showing unusually (yellowbrown) dark carapace colour (see Marsh et al 2015), indicating hydrothermal deposition on the exoskeleton. Specimens also showed black spots or areas along carapace margins and on leg segments, indicative of necrosis.…”
Section: Sampling Of Ovigerous Femalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Marsh et al . () found that this species, very shortly to be officially named Kiwa tyleri (Thatje et al . in press), inhabits different zones of the vent field depending on their sex and their reproductive stage.…”
mentioning
confidence: 99%